Effects of Tuina combined with traditional Chinese exercises on function disability in patients with lumbar disc herniation: a multicentre, randomised, controlled clinical trial - Liao, Yitao; Wang, Yi; Fan, Zhihong; Zhu, Qingguang; Zhou, Xin; He, Dandan; Li, Chao; Zhang, Xian (Frontiers in Neurology, 2025)
BackgroundLow back pain and leg pain are common symptoms of lumbar disc herniation (LDH), which predispose patients to walking dysfunction and affect their quality of life. Tuina and Traditional Chinese Exercises (TCEs) are often used in China as passive or active treatments to alleviate the symptoms of LDH in patients and to address disability. However, high-quality multicentre clinical trials evaluating the short- and long-term efficacy of Tuina combined with TCEs in the treatment of LDH are lacking.MethodsIn a multicentre, randomised, controlled clinical trial, 166 patients with LDH were recruited from four centres and randomly assigned into two groups that were treated with TCEs and Tuina combined with TCEs. Each group received intervention 3 times in 1 week for 4 weeks, and efficacy was assessed at baseline, 4 weeks of treatment, 12 weeks of follow-up and 24 weeks of follow-up. The primary outcome indicator assessed was the Oswestry Disability Index (ODI), and the secondary outcome indicators were the Visual Analogue Scale (VAS), the Short Form of Quality of Life (SF-36) Scale, the Short-Form McGill Pain Questionnaire (SF-MPQ) Scale and gait analysis.ResultsA total of 157 subjects completed the trial, and 9 were dislodged. After 4 weeks of intervention, the ODI mean value in the Tuina combined with TCE group was 16.31 (4.18), a decrease of 7.75 (95%, 6.88–8.62) from baseline. The mean value in the TCE group was 20.23 (3.43), a decrease of 3.79 (95%, 2.92–4.67) from baseline. The ODI scores were significantly lower in the Tuina combined with TCE group compared with the TCE group at weeks 4, 12 and 24, with mean differences of 3.92 (95%, 2.75–5.09, p < 0.001), 2.90 (95%, 1.63–4.18, p < 0.001) and 3.03 (95%, 1.70–4.36, p < 0.001), respectively. The Tuina combined with TCE group also performed significantly better than the TCE group in the VAS, SF-MPQ, SF-36 and gait analysis.ConclusionTuina combined with TCE therapy can effectively improve function disability, pain, quality of life and pace of step in patients with LDH, and the combined therapy is superior to single TCE therapy.Clinical trial registrationChiCTR2300077361; https://www.chictr.org.cn/showproj.html?proj=209956.